Dynamic essential oil composition of sunflower anther's capitate glandular trichomes during the reproductive development - Mazzei, Mariana Paola (2025)
Capitate glandular trichomes (CGTs) of sunflower (Helianthus annuus L.) are epidermal structures that facilitate interactions between the plant and various floral visitors. This study aimed to investigate the essential oil composition of an anther´s CGTs during different reproductive stages of the sunflower capitulum. We examined the late development of CGTs using differential interference contrast and confocal microscopy to identify the secretory and post-secretory stages of glands during anthesis and post-anthesis of the disc flowers in a sunflower genotype with a high number of CGTs per anther (a fertility restorer, Rf975). Additionally, we analyzed, for the first time, the chemical composition of essential oils secreted by CGTs during anthesis and post-anthesis using gas chromatography–mass spectrometry (GC–MS) on plants grown under field conditions. The GC–MS analysis from CGTs identified 13 organic compounds and their varying proportions at disc flower´s anthesis and post-anthesis. Proportions of Phytol and Hexadecanal were significantly higher during anthesis than post-anthesis. Moreover, we observed an increase in monoterpenoids and sesquiterpenoids at post-anthesis. Among these, α-Pinene and β-Gurjunene were the most abundant compounds in their respective groups. Our investigation reveals phenophase-dependent changes in the essential oil composition of sunflower anther CGTs. These findings suggest a dynamic “chemical code” generated by these glands, which may enhance communication with beneficial insects during anthesis (e.g., pollinators) and subsequently transition to a defensive function against post-pollination threats (e.g., herbivores).